Fatwas and Fags: Violence and the Discursive Production of Abject Bodies - Alzaid, Barrak (Columbia Journal of Gender and Law, 2010)
A recent New York Times article sports the headline, Iraq’s Newly Open Gays Face Scorn and Murder, and describes the violent backlash against the growing “gay subculture” that arose in the wake of the United States’s security interventions in Iraq. Such rhetoric establishes gay as a nascent community, rendered undeniably visible by violence and threats of physical harm. This visibility is typified by the political work of Iraqi LGBT, an Iraqi-led United Kingdom based organization that advocates for equal rights within Iraq. Although activist discourses express outrage that the killings remain largely unaddressed in spite of democratic rule, violence is not actually incongruous with the current juridico-democratic structures installed by the United States in Iraq. In 2005, Ayatollah Sistani, an independent religious scholar with a considerable base of Shiite supporters in Iraq, issued a fatwa on his website, www.sistani.org, that condemned al-lowat, a term later translated by activist groups and news media as “homosexual” or “gay.” The fatwa, an interpretation of the Qur’an and the Prophet Muhammed’s teachings, has the potential to define everyday practices and modes of being for that religious leader’s followers. Although any Muslim can technically follow any fatwa, the norms and practices of their particular community will determine whether they carry it out. While Western media gravitated toward this fatwa as the primary cause of the violence directed against homosexuality, Human Rights Watch, which recently published an extensive report on the violence, could find no direct causal link between the fatwa and the violence. The report acknowledges that in late 2005, the website, which showcased the fatwa in question in this Article, responded to a question asking “what is the judgment for sodomy?” by calling it forbidden and calling for punishment. However, the report relates that “[The fatwa] received little or no notice in the Iraqi press.” Rather, the report cites testimony that attributes the predominance of the violence to the Mahdi Army who “[turned] its attention at irregular intervals since 2004 to what it saw as sexual immorality in Iraq.” In the case of contemporary Iraq, both Sistani’s religious exegesis and the Mahdi Army’s rhetoric reflect a trajectory of conservative morals around sexuality that emerged with the rise of Islamism in the late 1970’s and which came about as a result of the Iranian Islamic Revolution. However, religious rhetoric cannot simply bear the responsibility for propagating violence. Instead, such rhetoric reflects what Raymond Williams termed “structures of feeling” or affect: tropes of emotion that inhabit and reflect lived experiences. In Williams’s estimation, structures of feeling, rather than world view or ideology, are concerned with “meanings and values as they are actively lived and felt.” The fatwa, rife with its condemnation of homosexuality, was issued in the political and juridical context of the Iraqi democratic transition. In this environment, the fatwa’s very rhetoric operates affectively to produce and regulate anxieties around sexuality, morality and national identity.